DEVELOPING COGNITIVE DEVELOPMENT OF CHILDREN USING COMBINATION OF RECTION MODEL OF GROUP B1 AT ISLAMIC BAKTI 1 BANJARMASIN - Radiansyah Radiansyah (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2021)
The problem of this research is the low cognitive ability of children in classifying objects based on colour, shape and size. The research aims to describe teacher activities, children's activities and analyze the results of children's cognitive development. The research approach uses qualitative research with Classroom Action Research in four meetings. The results showed that the teacher's activity at the last meeting got a maximum score of 32 with a percentage of 100% with very good criteria. Children's activities at the first meeting reached the category of a small number of active children, the second meeting reached the category of some active children, the third meeting reached the category of most active children and the fourth meeting reached the category of all active children. The classical achievement of children's development at the first meeting reached 20%, the second meeting reached 60%, the third meeting reached 80% and the fourth meeting reached 100%. Based on the results of the study, it was concluded that the combination of the Rection Riasantri model could increase the activity and developmental outcomes of children. It is suggested that the Rection Riasantri model can improve children's abilities in the cognitive aspect.Keywords: Cognitive, classifying objects based on colour, shape and size, Rection Riasantri.